Experimental evidence and theoretical approaches in unsaturated soils : proceedings of an International Workshop on Unsaturated Soils, Trento, Italy, 10-12 April 2000 /: proceedings of an International Workshop on Unsaturated Soils, Trento, Italy, 10-12 April 2000. ([2014?]) - Unknown
No abstract available